2011
DOI: 10.1177/0885066610395678
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Review: Interleukin-6 in Surgery, Trauma, and Critical Care: Part I: Basic Science

Abstract: A variety of cytokines play a role in the response to an inflammatory stimulus. The interleukin-6 (IL-6)-type cytokines are released in response to tissue injury or an inflammatory stimulus. They act locally and systemically to generate a variety of physiologic responses, principal among them is the acute phase response. The IL-6 type cytokines demonstrate pleiotropy and redundancy of actions. This is made possible by the distinctive characteristics of the IL-6 receptor complex, which contains an ubiquitous su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 87 publications
6
68
2
4
Order By: Relevance
“…These trigger a 'genomic storm' dominated by increased expression of interleukin (IL)-6, IL-1-receptor antagonist (IL-1RA), IL-8 (IL-8/CXCL8) and macrophage chemotactic protein-1 (MCP-1/CCL-2) [11]; mediators that mobilize neutrophil, monocyte and mesenchymal stromal cell (MSC) traffic [12][13][14][15]. IL-6 acts via both the hypothalamic-pituitary-adrenal axis to increase corticosteroid production and hepatocytes to initiate the acute phase response typified by increased activated protein-C [16]. Meanwhile, IL-1RA neutralizes IL-1β [17].…”
Section: Introductionmentioning
confidence: 99%
“…These trigger a 'genomic storm' dominated by increased expression of interleukin (IL)-6, IL-1-receptor antagonist (IL-1RA), IL-8 (IL-8/CXCL8) and macrophage chemotactic protein-1 (MCP-1/CCL-2) [11]; mediators that mobilize neutrophil, monocyte and mesenchymal stromal cell (MSC) traffic [12][13][14][15]. IL-6 acts via both the hypothalamic-pituitary-adrenal axis to increase corticosteroid production and hepatocytes to initiate the acute phase response typified by increased activated protein-C [16]. Meanwhile, IL-1RA neutralizes IL-1β [17].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 es la principal citoquina asociada a inflamación y la mayor responsable de la producción hepática de las diferentes proteínas de fase aguda, principalmente PCR. Esto permite emplear también a la PCR como marcador de daño, si bien su elevación en plasma va a ser lógicamente más tardía 12,13 . En nuestro estudio no hemos encontrado cambios significativos en la concentración de IL-1␤ y TNF-␣ a lo largo del tiempo.…”
Section: Discussionunclassified
“…Studies of the inflammatory profile over the peri-operative period have identified IL-6 as the key cytokine. IL-6 is released in response to any pro-inflammatory stimulus, such as tissue injury, and it acts locally and systemically to generate a broad panel of pleiotropic redundant responses (40,63,64). It is synthetized by endothelial cells, fibroblasts, and monocytes and stimulates B-cell differentiation and acute phase proteins expression.…”
Section: Peri-operative Cytokine Profilementioning
confidence: 99%